Correction: Eimanifar et al. Using ISSR Genomic Fingerprinting to Study the Genetic Differentiation of Artemia Leach, 1819 (Crustacea: Anostraca) from Iran and Neighbor Regions with the Focus on the Invasive American Artemia franciscana. Diversity 2020, 12, 132 - Amin Eimanifar; Alireza Asem; Pei-Zheng Wang; Weidong Li; Michael Wink (Diversity)
In the published publication [...]